Biomarker identification in HIV and non-HIV related lymphomas - Magangane, Pumza Samantha (Division of Anatomical Pathology, 2017)
DLBCL is the most common lymphoma subtype occurring in older populations as well as in younger HIV infected patients. The current treatment options for DLBCL are effective for most patients yet the relapse rate is high. While many biomarkers for DLBCL exist, they are not in clinical use due to low sensitivity and specificity. In addition, these biomarkers have not been studied in the HIV context. Therefore, the identification of new biomarkers for HIV negative and HIV positive DLBCL, may lead to a better understanding of the disease pathology and better therapeutic design. Initially differences in the clinicopathological features between HIV negative and HIV positive DLBCL patients were determined by conducting a retrospective study of patients treated at GSH. Subsequent to this, potential protein biomarkers for DLBCL were determined using MALDI imaging mass spectrometry (IMS) and characterised using LCMS. The expression of one of the biomarkers, heat shock protein (Hsp) 70, was confirmed on a separate cohort of samples using immunohistochemistry. Our results indicate that the clinicopathological features for HIV negative and HIV positive DLBCL are similar except for median age, and frequency of elevated LDH levels. Several clinicopathological factors were prognostic for all DLBCL cases including age, gender, stage and bone marrow involvement. In addition, tumour extranodal site was also a prognostic indicator for the HIV negative cohort. The biomarkers identified in the study consisted of four protein clusters including glycolytic enzymes, ribosomal proteins, histones and collagen. These proteins could differentiate between control and tumour tissue, and the DLBCL subtypes in both cohorts. The majority (41/52) of samples in the confirmation cohort were negative for Hsp70 expression. The HIV positive DLBCL cases had a higher percentage of cases expressing Hsp70 than their HIV negative counterparts. The non-GC subtype also frequently overexpressed Hsp70, confirming MALDI IMS data. Expression of Hsp70 correlated with poor outcome in the HIV negative cohort. In conclusion, this study identified potential biomarkers for HIV negative and HIV positive DLBCL from both clinical and molecular sources. These may be used as diagnostic and prognostic markers complementary to current clinical management for DLBCL.